703-P: Randomized Crossover Comparison of Automated Insulin Delivery vs. Conventional Therapy with Scheduled Stress Challenges - KAUR, RAVINDER JEET; DESHPANDE, SUNIL; PINSKER, JORDAN E.; MCCRADY-SPITZER, SHELLY K.; DESJARDINS, DONNA; CHURCH, MEI MEI; KREMERS, WALTER K.; DOYLE, FRANCIS J.; DASSAU, EYAL; KUDVA, YOGISH C. (Diabetes (New York, N.Y.), 2021)
Automated Insulin Delivery (AID) hybrid closed-loop systems have not been well studied in the context of psychological and physiological stress. We evaluated our interoperable artificial pancreas system with in-clinic stress challenges in a randomized crossover trial. Fourteen adults with type 1 diabetes were randomized to 2 weeks of AID-based control and two weeks of sensor augmented pump (SAP)l therapy at home in random order. The AID system used the Zone-Model Predictive Control algorithm with a continuous function of glucose velocity and insulin-on-board to gradually increase insulin infusion under conditions of sustained hyperglycemia. During each two-week period, in-clinic stress assessments for psychological stress (TSST and SECPT) and pharmacological stress (hydrocortisone 40-20-20 mg) were performed. Ten subjects completed the study per protocol, with 48 stress sessions completed in 12 subjects. AID increased time 70-180mg/dL from 63.1 to 74.4% (p=0.001), decreased time <70mg/dL from 1.5 to 0.8% (p=0.04) and decreased time >180mg/dL from 35.4 to 24.8% (p=0.001) during the 2 weeks outpatient use. AID decreased glycemic variability as measured by CV (p=0.037) and time <70mg/dL (p=0.014) during psychological stress (Table 1) AID improved glucose control during outpatient use and improved CV and % time <70mg/dL during in-clinic psychologic stress compared to SAP.